The Influence of SEA and E-WoM on The Decision To Study In The Digital Business Study Program, AL-Irsyad University Cilacap - Fajar Nur Wibowo; Zulfikar Yusya Mubarak; Nuni Wulansari; Annisa Rahayu P; Dani Setyawan (Proceeding of The International Conference on Business and Economics, 2023)
This study aims to analyze the influence of SEA and E-WoM on college decisions for Digital Business Study Program, Universitas Al Irsyad Cilacap, The object of this research is the Digital Business Study Program at Al-Irsyad Cilacap University, while the subjects are students of the Digital Business Study Program at Al-Irsyad University Cilacap. sampling with purposive sampling technique. The number of samples in this study were 31 respondents. Data was obtained through questionnaires which were distributed directly to digital business students at Al-Irsyad University, Cilacap. The data analysis technique uses SPSS version 22. Based on the results of the analysis carried out, it shows that SEA has a positive effect on digital business study study decisions, E-WoM has a positive effect on digital business study study decisions.